2006
DOI: 10.3130/jaabe.5.361
|View full text |Cite
|
Sign up to set email alerts
|

A Two Year Measurement of Energy Consumption and Indoor Temperature of 13 Houses in a Cold Climatic Region of Japan

Abstract: The energy consumption and indoor temperature of 13 housing units sited in the northern region of Honshu Island, Japan were investigated for a full two years from Dec. 2002 to Nov. 2004. Five of the houses were installed with all-electric equipment. The annual and daily energy consumption profiles of two typical houses were analyzed, and the annual energy consumption per house was found to range from 40GJ/year to 120GJ/year. The difference of energy consumption between the two years was very small, while in so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 8 publications
0
4
0
1
Order By: Relevance
“…The AC electricity usage in most of the targeted dwellings is positively correlated with outdoor temperature, for which the correlation coefficient ranged from -0.1 to 0.5. Yoshino et al, [25] also revealed a strong correlation between the cooling energy consumption and the outdoor temperature.…”
Section: Correlation Of Ac Consumption With Outdoor Temperaturementioning
confidence: 93%
“…The AC electricity usage in most of the targeted dwellings is positively correlated with outdoor temperature, for which the correlation coefficient ranged from -0.1 to 0.5. Yoshino et al, [25] also revealed a strong correlation between the cooling energy consumption and the outdoor temperature.…”
Section: Correlation Of Ac Consumption With Outdoor Temperaturementioning
confidence: 93%
“…Choi, I. Y., Cho, S. H., dan Kim, J. T. 2012 Haas, et al (1998) dalam Ouyang, J., et al (2009) menjelaskan bahwa perilaku pengguna merupakan faktor yang paling berpengaruh terhadap konsumsi energi rumah tangga. Yoshino, H., et al (2006) mengklasifikasikan 6 kategori konsumsi energi, yaitu sistem penghawaan, penyediaan air panas, dapur, audio visual/ informasi, perawatan kesehatan, pencahayaan, dan sebagainya.…”
Section: Tinjauan Pustakaunclassified
“…A study on energy consumption for residential buildings in Japan carried out by the Architectural Institute of Japan (AIJ, 2006), which included an internet questionnaire survey of 4,000 households and detailed on-site investigations of 80 houses throughout Japan. And the two years detailed monitoring of energy consumption and indoor temperature of 13 housing units in the northern region of Honshu Island, Japan, by Yoshino et al (2006). Although these types of questionnaire surveys and long-term on-site measurements provide accurate data, they are very costly and time consuming.…”
Section: Methodsmentioning
confidence: 99%